Sosialisasi pentingnya social distancing dan mencegah pola hidup dalam upaya memutus rantai penyebaran covid-19 - Maria Herlinda Dos Santos; Hasnah Hasnah; Umrah Bahar (Rengganis Jurnal Pengabdian Masyarakat, 2021)
Covid-19 is one of the outbreaks whose spread is very significant in human life today, almost all circles discuss and anticipate this outbreak in various ways, some are washing their hands all the time using soap, some are cleaning their hands by using a hand sanitizer, some even do sports and maintain their diet so that their immunity is maintained during this pandemic. Given that Covid-19 is transmitted through physical contact and regardless of age and sex. Therefore, apart from exercising and adjusting our diet, we are also obliged to have adequate rest. In this community service activity aimed at Karang Taruna to participate in the socialization of "The Importance of Social Distancing and Preventing Lifestyles in Efforts to Break the Chain of Covid-19 Spread in Tarowang Village, Tarowang District, Jeneponto Regency". The method used is door-to-door socialization with attention to distance when communicating with the community with partners, namely Tarowang Village Youth Organization, Tarowang District. As a result of this activity, the community and Karang Taruna take part in participating and getting the benefits of social distancing and a healthy lifestyle.